2016
DOI: 10.1210/en.2015-1549
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin as an Adjunct for Type 1 Diabetes Immunotherapy

Abstract: Type 1 diabetes is caused by autoimmune destruction of β-cells. Although immunotherapy can restore self-tolerance thereby halting continued immune-mediated β-cell loss, residual β-cell mass and function is often insufficient for normoglycemia. Using a growth factor to boost β-cell mass can potentially overcome this barrier and prolactin (PRL) may fill this role. Previous studies have shown that PRL can stimulate β-cell proliferation and up-regulate insulin synthesis and secretion while reducing lymphocytic inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…1B), although the average blood glucose of the aCD3-alone group tended to be higher than the aCD3 + OFS group throughout the IPGTT. The non-diabetic normal control mice and the aCD3-alone group had similar responses during the IPGTT and ITT, as we previously observed27. Of note, the aCD3-alone and the aCD3 + OFS groups had similar body weights at the time of sacrifice (aCD3: 23.08 ± 0.43 g vs. aCD3 + OFS: 23.35 ± 0.23 g).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…1B), although the average blood glucose of the aCD3-alone group tended to be higher than the aCD3 + OFS group throughout the IPGTT. The non-diabetic normal control mice and the aCD3-alone group had similar responses during the IPGTT and ITT, as we previously observed27. Of note, the aCD3-alone and the aCD3 + OFS groups had similar body weights at the time of sacrifice (aCD3: 23.08 ± 0.43 g vs. aCD3 + OFS: 23.35 ± 0.23 g).…”
Section: Resultssupporting
confidence: 79%
“…We chose OFS because studies have shown that it improves insulin sensitivity in obesity1115282930, which may result in lower insulin requirement and improved glucose homeostasis. Our immunotherapy of choice was the anti-CD3 monoclonal antibody (aCD3) because it is a well-characterized agent that induces permanent diabetes remission in up to 60% of NOD mice452731, and it has been used in several human trials, demonstrating some efficacy in slowing the process of beta-cell destruction67832. In this study, we found that when given in conjunction with aCD3, OFS improves the aCD3-mediated diabetes reversal rate in NOD mice, accompanied by an improvement in insulin sensitivity, a reduction in insulitis, and an increase in beta-cell proliferation rate and insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some peptide hormones, including parathyroid hormone-related protein (PTHrP) [31,32] and prolactin [33,34], stimulate β-cell replication in vitro and are known mitogens of compensatory β-cell proliferation during rodent pregnancy. Recently it was shown that PRLR-Jak2-Stat5 signaling is not prominent in human β-cells; interestingly, however, murine Stat5a induced proliferation of human β-cells [15] and there is evidence that prolactin may augment traditional T1D therapies [35]. Signaling of steroid hormones progesterone, estrogen, and androgen modulates proliferation, and is disrupted under diabetic conditions [14,34].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies in this latter experimental model showed that PRL treatment enhances a Th2 response by increasing the frequency of IL-10 positive splenocytes and down-modulating the featured expression of the Th1 cytokines IFN-γ and TNF-α in splenocytes ( 231 ). Furthermore, PRL-expanded Treg (CD4 + Foxp3 + ) population and improved the efficacy of short-term low-dose anti-CD3 treatment (which induce a transient CD4 + and CD8 + T cell depletion) at achieving diabetes remission in the NOD mice ( 232 ). Conversely, severe hyperprolactinemia induced by anterior pituitary ectopic transplantation increases the incidence of diabetes in the NOD mice ( 233 ).…”
Section: Hormones Neuropeptides and Neurotransmitters Modulate T Cementioning
confidence: 99%